+0  
 
0
60
1
avatar

If we express $3x^2 - 6x - 2$ in the form $a(x - h)^2 + k$, then what is $a + h + k$?

 Jan 19, 2021
 #1
avatar+116126 
+2

3x^2  - 6x  -  2              factor out the 3

 

3 ( x^2  - 2x  - 2/3)      

 

Take 1/2 of 2  = 1  square it  =1......add and subtract within the parentheses

 

3 ( x^2  - 2x + 1   -2/3  -1)           factor the first three terms.....simplify the  rest

 

3 [ ( x  -1)^2   - 5/3  ]         distribute the "3" across the terms in brackets

 

3( x - 1)^2  -  5

 

a =  3

h = 1

k = -5

 

And their sum  =    -1

 

cool cool cool

 Jan 19, 2021

82 Online Users

avatar
avatar
avatar
avatar